2020
DOI: 10.1055/s-0040-1715514
|View full text |Cite
|
Sign up to set email alerts
|

Retorno ao esporte após osteotomia tibial alta com método de cunha de abertura

Abstract: Resumo Objetivo Avaliar o retorno ao esporte em pacientes jovens e ativos praticantes de alguma modalidade esportiva submetidos a osteotomia tibial alta (OTA) com o método de cunha de abertura. Métodos Foram analisados prospectivamente 12 pacientes submetidos ao procedimento de OTA utilizando-se método de cunha de abertura. Todos os pacientes estavam afastados do esporte. Foram utilizados os escores Lysholm, questionário International Knee Documentation Committee (IKDC, na sigla em inglês),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Moreover, our study showed that the return to sports rate in the OWHTO + Repair group was higher than that in the OWHTO group. A high rate of return to sports was reported in both older and young patients who underwent OWHTO [30,32,33]. Otoshi et al [33] reported that most older patients (aged ≥ 70 years) returned to the sports level after OWHTO (return to sports rates: 93%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our study showed that the return to sports rate in the OWHTO + Repair group was higher than that in the OWHTO group. A high rate of return to sports was reported in both older and young patients who underwent OWHTO [30,32,33]. Otoshi et al [33] reported that most older patients (aged ≥ 70 years) returned to the sports level after OWHTO (return to sports rates: 93%).…”
Section: Discussionmentioning
confidence: 99%
“…It was with interest that I read the article entitled “Retorno ao esporte após osteotomia tibial alta com método de cunha de abertura” by Nicolini et al 1 (Rev Bras Ortop 2021;56(3):313–319). The authors demonstrate the results of returning to sport of 12 patients submitted to this procedure after a 12-month follow-up.…”
mentioning
confidence: 99%
“…Foi com interesse que li o artigo intitulado “Retorno ao esporte após osteotomia tibial alta com método de cunha de abertura” dos autores Nicolini et al 1 (Rev Bras Ortop 2021;56(3):313–319). Os autores demonstram os resultados de retorno ao esporte de 12 pacientes submetidos a este procedimento após seguimento de 12 meses.…”
unclassified